2016
DOI: 10.21661/r-112631
|View full text |Cite
|
Sign up to set email alerts
|

Main approaches to the study of loss

Abstract: this article presents the main approaches to the concepts of grief and loss study. The article describes the contribution of E. Lindemann, Z. Freud, J. Bowlby, F.E. Vasiluk, and E. Kubler-Ross. Moreover, the research also contains the main forms of grief and some stadial models within the perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Grieving (Petrovskaya, 2016) consists in the gradual release of "Ego" from complete immersion in the memories of the lost significant and return to material reality. It was revealed that almost all the models of loss experience studied (Burina, 2016;Gross, 2018) contained such key phases as shock, denial, depression, and acceptance with no clear boundaries. Thus, we consider loss as an individual process, and to pass one a person has to live through several phases with the own needs each.…”
Section: The Process Of Loss Experience and The Gestalt Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Grieving (Petrovskaya, 2016) consists in the gradual release of "Ego" from complete immersion in the memories of the lost significant and return to material reality. It was revealed that almost all the models of loss experience studied (Burina, 2016;Gross, 2018) contained such key phases as shock, denial, depression, and acceptance with no clear boundaries. Thus, we consider loss as an individual process, and to pass one a person has to live through several phases with the own needs each.…”
Section: The Process Of Loss Experience and The Gestalt Approachmentioning
confidence: 99%
“…Foreign psychological studies that are devoted to the process of loss experience (Gentry et al, 2017;Hamilton, 2016) are mostly aimed at studying the adaptive abilities of a person at the time of loss experience. As for Russian psychologists (Baeva, 2016;Burina, 2016;Karacheva & Magomed-Eminova, 2017), their works mainly address the issues of providing short-term psychological assistance in the event of various kinds of extreme situations. Despite the existing scientific research on this phenomenon, there is currently a lack of research in the field of providing long-term psychological assistance and accompanying the process of loss experience.…”
Section: Problem Statementmentioning
confidence: 99%